‘SCIENCE MOTIVATION’ ANALYSIS OF ELEMENTARY STUDENTS - Erviana, N; Roshayanti, F; Priyanto, H (Universitas Pendidikan Ganesha, 2019)
Based on the results of the PISA study in 2015 the level of science education in Indonesia has increased but not all regions have been surveyed properly. The low education in Demak Regency and the low interest of students in science subjects indicates the lack of student motivation towards science. The focus of this research is to find out the results of the analysis of Science Motivation of fifth grade elementary school students in Mijen District, Demak Regency on the Value of Career aspect. This research was conducted at public elementary schools in Mijen sub-district, Demak Regency. The population of this research is the fifth grade students of the 2018/2019 school year with a total sample of 198 students. The method used in this study consisted of observation and questionnaire questionnaire. Using a questionnaire instrument adapted from the SMQ (Science Motivation Questionnaire). Based on the results of the study it can be concluded that Science Motivation of fifth grade elementary school students in Mijen District, Demak Regency in the Value of Career aspect is categorized in the